PENGUNGSI, UKIP, DAN EUROSKEPTISME: MEMAHAMI EKSISTENSI KEAMANAN DI INGGRIS TAHUN 2016 - Idrus, Muh. Rizky Hikmatullah; Pahlawan, Harisa Firdaus (Universitas Jenderal Ahmad Yani, 2024)
This research aims to analyze the form of security threats built through the relational relationship between refugees, UKIP, and Euroscepticism in the UK, as well as the formation of the discourse of security threats that occurred in the UK in 2016, using the theories of securitization, economic security, and Euroscepticism. The research method used in this article is descriptive-analytic, with data collection techniques in the form of a literature review sourced from books, journals, articles, official internet sites, and reports related to this research. The results of this study show that the presence of refugees in the UK creates economic inequality due to unequal economic distribution and is signaled as an economic threat as a referent object. The entry of Euroscepticism in the UK has influenced the public opinion of the UK society, which makes it easier for the right-wing party UKIP to exist and be popular